KOMUNIKASI PERSUASIF ICA (INDONESIAN CAT ASSOCIATION) CABANG PEKANBARU DALAM MEREKRUT PECINTA KUCING DI KOTA PEKANBARU - Khairunnisa, Hasveni; ", Nurjanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
ICA is a cat lover organization that integrated under international cat federation, FIFe (Fédération Internationale Féline). According to growth and increasing of people enthusiasm on keeping cat, ICA tries to invite cat lover to join with ICA so they can have a place to learn about treating and caring cat. The recruiting effort can’t be apart from persuasive communication activity so that can arise adorableness, giving stimulus, and convince the cat lover to join with ICA. This research aims to find out persuader credibility, persuasive message, and media that be used on persuasive communication by ICA Branch Pekanbaru on recruiting cat lover in Pekanbaru.This research using qualitative research method with descriptive approach and using persuasive communication model of Applebeum & Anatol and AIDDA theory. The subject of this research was choosen using purposive technique who consists of Chairman, PR, and one member of ICA Branch Pekanbaru, and also three cat lovers in Pekanbaru. Data was collected through observation, interview and documentation. Data was analyst using interactive model of Miles & Huberman. Meanwhile the data validity technique includes extension of participation and triangulation.The result of this research showed first, credibility of ICA Branch Pekanbaru as persuader built through 3 aspects which are competent persuader, Expertness, and Trust Worthiness. Second, message consists of verbal message and nonverbal message. Verbal message is discourse material that delivered on educational training (Diklat), and also education/comprehension information about how to keeping and treating cat. Meanwhile the nonverbal message is uniform using and placing stuff that especially designed with cat picture and also feature ICA and FIFe logo, displayed some type of racial cat, and practiced how to treat and caring cat directly. Third, media utilizing consists of face to face communication that is meet the cat lover directly, and indirect communication through using of mass media which are brocure, banner, billboard, pamphlet, news paper, magazine, radio, television, and social media such facebook and Instagram. Besides that, ICA also use contact person (call and messaging) and personal social media account of each member.Key Words : Persuasive Communication, Indonesian Cat Association, Persuasive Communication Model of Applebeum & Anatol, AIDDA Theory